1973
DOI: 10.1139/v73-386
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylamino Acids in Peptide Synthesis. IV. Racemization and Yields in Peptide-bond Formation

Abstract: The racemization of an N-methylamino-acid residue during peptide-bond formationand mixed-anhydride activation has been investigated using Ala-MeLeu-Gly and Ala-MeLeu as model peptides. The results were compared with those for Ala-Leu-Gly, Ala-Leu, and Ala-Pro. The extents of racemization were determined by analysis of the diastereomeric products of the reactions after deprotection, using an amino-acid analyzer. Extensive racemization was detected after the hydrolysis of the mixed anhydrides of Bz-MeLeu, Z-Ala-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 19 publications
0
50
0
1
Order By: Relevance
“…The use of alkaline conditions in the formation of the N-methyl group and removal of the methyl ester causes varying degrees of undesired epimerization [32][33][34]. Therefore, a direct route to N-methyl amino acids 19 was accomplished without esterification by lowering the reaction temperature to 0 C. McDermott and Benoiton [35] found that reaction temperature was an important factor in avoiding the formation of methyl esters (Scheme 6.8) and also identified acidic reaction conditions other than basic conditions that caused epimerization of N-methyl amino acid-containing dipeptides.…”
Section: Base Mediated Alkylation Of N-nitrobenzenesulfonamidesmentioning
confidence: 99%
“…The use of alkaline conditions in the formation of the N-methyl group and removal of the methyl ester causes varying degrees of undesired epimerization [32][33][34]. Therefore, a direct route to N-methyl amino acids 19 was accomplished without esterification by lowering the reaction temperature to 0 C. McDermott and Benoiton [35] found that reaction temperature was an important factor in avoiding the formation of methyl esters (Scheme 6.8) and also identified acidic reaction conditions other than basic conditions that caused epimerization of N-methyl amino acid-containing dipeptides.…”
Section: Base Mediated Alkylation Of N-nitrobenzenesulfonamidesmentioning
confidence: 99%
“…It is known that N-methylamino acids are particularly susceptible to racemization [53]. For this reason a facile procedure for configurational analysis and for determination of the degree of racemization is highly desirable.…”
Section: N-methyl Amino Acidsmentioning
confidence: 99%
“…Davies& Mohammed 1131 with the aid of NMR-techniques came to the same conclusion studying the racemization in N-methylated amino-acid derivatives during peptide coupling in a model dipeptide system. They could as McDermott & Benoiton [12] confirm that the source of the racemization involving dicyclohexylcarbodiimide (DCCI) at room temperature is the oxazolonium intermediate i.…”
mentioning
confidence: 99%